Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Keputusan Pembelian Produk Herbalife Nutrition di Ghidza Club Cibinong - Gena; Nurjanah, Rina (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
The aim of this research is to determine and analyze the influence of product quality, service quality and price on purchasing decisions for Herbalife Nutrition products at Ghidza Club Cibinong. The type of research used is quantitative research in the form of an associative strategy with research methods in the form of data collection using questionnaires, observations and interviews. The data analysis model used is multiple linear regression analysis. The sample consists of 50 respondents. The results of the regression test show that 84.5% of purchasing decision factors can be explained by Product Quality, Service Quality and Price while the remaining 15.5% is explained by other factors not examined in this research. meanwhile, the results of the F test show that simultaneously the variables Product Quality, Service Quality and Price simultaneously have a positive and significant effect on purchasing decisions with the analysis results being the value Fcount (90.133) > Ftable (2.790). The results of the t test show that the product quality variable shows the results of t-count analysis (7.252), the service quality variable shows the results of t-count analysis (3.466), and the price variable shows the results of t-count analysis (2.368), where ttable (2.011) then partially the three variables this has a positive and significant effect on the decision to purchase Herbalife Nutrition products at Ghidza Club Cibinong. The dominant variable influencing purchasing decisions is product quality.